An investigation of preparation of continuous carbon fiber reinforced PLA prepreg filament. (April 2023) - Wang, Qing; Zhang, Qing; Kang, Yuzhu; Wang, Yesong; Liu, Jiang
Abstract: Continuous fiber reinforced thermoplastic composite (CFRTC) 3D printing technology has been a hot research topic in the field of additive manufacturing in recent years. This technology greatly improves the mechanical properties of printed parts by adding continuous reinforced fiber to the thermoplastic polymer. This paper investigates the production of prepreg filaments for "independent extrusion" type Fused Deposition Modeling (FDM) 3D printing. Firstly, suitable impregnation process and materials are selected, and not only the overall design of the prepreg equipment is carried out but also combined with the impregnation theory and simulation to determine the structure of each impregnation mould. Finally, based on the prepreg equipment, continuous carbon fiber reinforced PLA prepreg filament is made. And 3D printing test was conducted. The equipment successfully manufactured continuous carbon fiber reinforced PLA prepreg with a diameter of about 0.38 mm and a monofilament tensile strength of 1200 MPa. The tensile strength of the printed parts reached 620 MPa by printing through an independent extrusion type 3D printer. Highlights: A machine was designed to impregnate continuous dry fibers with matrix. The pre-impregnated fibers are suitable for printing on FDM independent extrusion 3D printers. The article analyzes each part of the prepreg mould by means of mechanism analysis and simulation. The relationship between the process parameters during filament making process was investigated by using the prepreg fiber diameter and tensile strength. The optimal impregnation parameters were obtained. Monofilament tensile strength was obtained by monofilament tensile test. The filaments impregnated with the optimal parameters are 3D printed into samples. Through the tensile test, the tensile properties and the section expansion rate of the prepreg composite printing specimens are investigated.